Medical records completeness: can Link Professionals improve quality in a Rehabilitation Hospital?. (13th November 2019) - Scarpis, E; Poletto, M; Guardini, I; Dal Bo, O; Maestra, M R; Tea, G P; Zampa, A; Lattuada, L; Castriotta, L; Brusaferro, S
Abstract: Background: The completeness of Medical Record (MR) is an indicator of the quality of care provided. IMFR (Medical and Physical Rehabilitation Institute), a hospital part of the Udine Healthcare Trust with 400 discharges yearly, launched at the end of 2017 a MR-quality program based on the involvement of Link Professionals (LP): doctors, nurses and therapists specifically trained. The main aim of this study is to determine if involving LP would improve MR completeness and would keep it over time. The second aim is to describe the 1-year experience of MR completeness and professional attitude toward recording medical information in it. Methods: In December 2017 a new MR was introduced at the IMFR and its completeness was evaluated in January 2018. From January to April 2018, 17 LP educated all colleagues on the recording behavior through periodic meetings and focus groups. Then, LP peer-reviewed 20 inpatients paper-based MRs, assessing completeness, in April 2018 and then quarterly until January 2019. The evaluation was performed with a tool including a total of 73 items, divided in pertinence to the three professional figures involved. Feedbacks on MR completeness were given to professionals by LP in two-weeks. External data validation was performed to ensure data consistency. Significance (p < 0.01) was assessed by Cochran-Armitage test for trends. Results: The overall completeness of MR improved significantly from 59.6% (552 items out of 926; Jan-18) to 77.0% (738/959; Apr-18), settling to 78.3% (696/889) in January-19, with an overall trend of + 18.7%. Items pertaining to doctors improved significantly from 56.4% (217/385) to 81.4% (1173/1441), nurses' from 60.7% (165/272) to 78.6% (740/941), therapists' from 79.0% (79/100) to 91.7% (277/302). External validation results in 75% of agreement. Conclusions: The involvement of LP proved effectiveness in encouraging professionals behavior, supporting the MR completeness improvement and keep it over one year time. Key messages: Professionals involvement and short-term feedbacks contribute to the healthcare quality improvement. Peer-reviewing medical records improves professionals attitude in recording behavior.